Efficacy and safety of neoadjuvant imatinib therapy for patients with locally advanced rectal gastrointestinal stromal tumors: A multi-center cohort study - Li, Weihao; Li, Xinyue; Yu, Kun; Xiao, Binyi; Peng, Jianhong; Zhang, Rongxin; Zhang, Lingfang; Wang, Kun; Pan, Zhizhong; Li, Cong; Wu, Xiaojun (Frontiers in Pharmacology, 2022)
Background: Several issues on neoadjuvant imatinib therapy remain controversial despite its widespread application for rectal gastrointestinal stromal tumors (GIST). We aimed to describe the clinicopathological characteristics of this specific population, and compare the surgical and oncologic outcomes between patients with or without neoadjuvant imatinib therapy. Patients and Methods: A cohort of 58 consecutive locally advanced rectal GIST patients receiving surgical treatment between January 2007 and July 2019 at Sun Yat-sen University Cancer Center and Yunnan Cancer Hospital was retrospectively analyzed. Recurrence free survival (RFS) and overall survival (OS) were estimated using Kaplan-Meier method. Results: There were 33(56.9%) patients who received neoadjuvant imatinib therapy. Among them, 20(60.6%) patients had partial response (PR) as their best response, 11(33.3%) patients had stable disease (SD), and 2(6.1%) patients had progressive disease (PD). The median tumor size reduced from 5.2 cm to 4.0 cm after treatment (P < 0.001) ,and an attained “maximal response” was primarily achieved (32/33) on the 12th month after treatment. The most common adverse event was anemia. There were 27 adverse events occurred, most of which were grade 1 (19/27). With respect to intraoperative and postoperative surgical outcomes, no significant difference was found between patients with or without neoadjuvant Imatinib therapy except that patients with neoadjuvant treatment had a significant higher rate of preventive ileostomy (P = 0.004). Patients received neoadjuvant treatment had a superior 2-year RFS outcome than those without, though the difference was no significant (91.7% vs. 78.9%, P = 0.203). there were no significant differences in the 2-year OS rates (95.2% vs. 91.3%, P = 0.441). Conclusion: Neoadjuvant imatinib therapy is an effective and safe treatment for locally advanced rectal GISTs. Further studies are warranted to validate the long-term prognostic benefit for patients with rectal GISTs receiving neoadjuvant imatinib therapy.